1996
DOI: 10.1007/bf02257571
|View full text |Cite
|
Sign up to set email alerts
|

Soil structure and plant growth: Impact of bulk density and biopores

Abstract: Compacted soils are not uniformly hard; they usually contain structural cracks and biopores, the continuous large pores that are formed by soil fauna and by roots of previous crops. Roots growing in compacted soils can traverse otherwise impenetrable soil by using biopores and cracks and thus gain access to a larger reservoir of water and nutrients. Experiments were conducted in a growth chamber to determine the plant response to a range of uniform soil densities, and the effect of artificial and naturally-for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
170
0
25

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(204 citation statements)
references
References 38 publications
9
170
0
25
Order By: Relevance
“…water transmission and storage pores. Stirzaker et al (1996) reported improved barley root penetration through a compacted soil layer via biopore channels created weather artificially or by ryegrass and lucerne. Nuttall et al (2008) considered that primer plants with a highly branched root systems, e.g.…”
Section: Organic Matter Inputmentioning
confidence: 99%
See 1 more Smart Citation
“…water transmission and storage pores. Stirzaker et al (1996) reported improved barley root penetration through a compacted soil layer via biopore channels created weather artificially or by ryegrass and lucerne. Nuttall et al (2008) considered that primer plants with a highly branched root systems, e.g.…”
Section: Organic Matter Inputmentioning
confidence: 99%
“…Perkons et al (2014) measured higher root length density of main crops such as wheat, barley and rapeseed in deep soil following a taproot species compared to a fibrous rooted pre-crop and related this to enhanced largesized biopores. Stirzaker et al (1996) mentioned the problem of root-soil contact for roots growing in large biopores. White and Kirkegaard (2010) studied this problem in detail, showing that wheat roots growing in biopores interacted with surrounding soil by root hairs, while roots growing in cracks had reduced root hair formation.…”
Section: Organic Matter Inputmentioning
confidence: 99%
“…Entretanto, no menor conteúdo de água, os componentes de produtividade demonstram que a compactação foi prejudicial ao desenvolvimento da cultura, nos dois solos. STIRZAKER et al (1996) obtiveram resultados semelhantes em cevada cultivada em casa-devegetação. Estes autores verificaram que, em maiores conteúdos de água, a densidade do solo intermediária proporcionou maior desenvolvimento de cevada e que, em solos mais secos, a menor densidade do solo foi mais favorável ao desenvolvimento da cultura.…”
Section: Resultsunclassified
“…Este autor afirma que a absorção de água pelas raízes ocorre em um raio médio de 0,02m. Em casa-de-vegetação foi observado maior desenvolvimento de cevada no menor valor de densidade do solo, em condição de menor conteúdo de água (STIRZAKER et al, 1996). Neste sentido, DEXTER (1987) afirma que o crescimento pode ser inibido na resistência à penetração de 1MPa em solo seco, no entanto, em solo úmido, pode haver crescimento em valores de resistência à penetração superiores a 4MPa.…”
Section: Resultsunclassified
See 1 more Smart Citation